Men’s Names as a Way to Create a Chronotope in the Novel P. Ivanchenko «Anger of Perun» (Linguostylistic Studies, 2015)
The article analyzes the male names in the historical novel R. Ivanchenko «Anger of Perun», because the proper names are chronotope in the historic work of the Kievan Rus'; It found that men's names are an onomastic writing a novel, and is closely related to the ideological and plot and thematic focus of the work. Kievan Rus appears in the novel thanks to the widespread use of onomastic vocabulary.Proper names of real historical personages in the novel are not uniform in their fame: it is not only proper names of famous people age, but also the people, the popularity of which is limited in time and space. Anthroponyms not only are an onomastic system works, and are the active part that determines the position in the formation and functioning of all onomasticon in fiction, including in terms of time and space continuum. All names are used to display the historical truth, large-scale images of historical events, a clear definition of the place and time of the work. Key words: anthroponym, proper names, idiostyle, chronotope, men’s names. References